Penile Mondor’s disease: a case report - M. Bolognesi (Italian Journal of Medicine, 2013)
CASE REPORT This article describes a case report with a review of the symptomatology diagnosis, and treatment of thrombophlebitis in the superficial dorsal vein of the penis. Penile Mondor’s disease is a benign condition, and after appropriate therapy, near complete recovery takes place within three weeks. DISCUSSION Thrombophlebitis of the superficial dorsal vein of the penis (Penile Mondor’s disease) is a rare, but important clinical diagnosis that any physician, and in particular general practitioners, should be able to recognize. Indeed, correct diagnosis and consequent reassurance can help to control the anxiety typically experienced by patients suffering from the disease.